An overview of postbiotics: unveiling their distinct role in gut health - Ali Ikram; Sheikh Zain Safdar; Muhammad Tayyab Arshad; Areeba Rasheed; Kodjo Théodore Gnedeka (Food and Agricultural Immunology)
The review explores the multifaceted impact of postbiotics on gut health, highlighting their impact on the immune system, gut flora, and general health. Postbiotics play a vital role as mediators in the complex interaction between the gut microbiota and various processes, such as the fermentation of carbohydrates and the creation of enzymes, peptides, and vitamins. A diverse range of microorganisms inhabit the human gastrointestinal tract and interact tightly with the mucosal immune system. The host’s immunological response, defense against infections, and delivery of various nutrients are all influenced by the gut microbiota, which is crucial to maintaining host health. Numerous studies show that probiotics and prebiotics have been linked to direct and indirect regulation of immune response and microbiota. This study demonstrated that postbiotics preserve microbiota balance and control the immune system, such as the bioactive metabolites generated by the gut microbiota and cell wall components produced by probiotics.